Factors associated with phosphatidylethanol (PEth) sensitivity for detecting unhealthy alcohol use: An individual patient data meta‐analysis. (7th May 2021) - Hahn, Judith A.; Murnane, Pamela M.; Vittinghoff, Eric; Muyindike, Winnie R.; Emenyonu, Nneka I.; Fatch, Robin; Chamie, Gabriel; Haberer, Jessica E.; Francis, Joel M.; Kapiga, Saidi; Jacobson, Karen; Myers, Bronwyn; et al.
Abstract: Background: Objective measurement of alcohol consumption is important for clinical care and research. Adjusting for self‐reported alcohol use, we conducted an individual participant data (IPD) meta‐analysis to examine factors associated with the sensitivity of phosphatidylethanol (PEth), an alcohol metabolite, among persons self‐reporting unhealthy alcohol consumption. Methods: We identified 21 eligible studies and obtained 4073 observations from 3085 participants with Alcohol Use Disorders Identification Test—Consumption (AUDIT‐C) positive scores (≥3 for women and ≥4 for men) and PEth measurements. We conducted 1‐step IPD meta‐analysis using mixed effects models with random intercepts for study site. We examined the associations between demographic (sex, race/ethnicity, and age) and biologic (body mass index—BMI, hemoglobin, HIV status, liver fibrosis, and venous versus finger‐prick blood collection) variables with PEth sensitivity (PEth≥8 ng/ml), adjusting for the level of self‐reported alcohol use using the AUDIT‐C score. Results: One third (31%) of participants were women, 32% were African, 28% African American, 28% White, and 12% other race/ethnicity. PEth sensitivity (i.e., ≥8 ng/ml) was 81.8%. After adjusting for AUDIT‐C, we found no associations of sex, age, race/ethnicity, or method of blood collection with PEth sensitivity. In models that additionally included biologic variables, those with higher hemoglobin and indeterminate and advanced liver fibrosis had significantly higher odds of PEth sensitivity; those with higher BMI and those living with HIV had significantly lower odds of PEth sensitivity. African Americans and Africans had higher odds of PEth sensitivity than whites in models that included biologic variables. Conclusions: Among people reporting unhealthy alcohol use, several biological factors (hemoglobin, BMI, liver fibrosis, and HIV status) were associated with PEth sensitivity. Race/ethnicity was associated with PEth sensitivity in some models but age, sex, and method of blood collection were not. Clinicians should be aware of these factors, and researchers should consider adjusting analyses for these characteristics where possible. Abstract : This is an analysis of data from 21 studies that included 3085 persons from four continents who reported unhealthy alcohol use. We found that the sensitivity of phosphatidylethanol (PEth), a blood alcohol biomarker indicating prior 2–4 weeks' alcohol use, increased with level of alcohol use, but did not vary by sex, race/ethnicity, or age. PEth sensitivity was lower for persons with higher body mass index, more severe anemia, and among persons with HIV infection. These factors may need to be considered in interpreting negative PEth results.